Mobile phones in young people everyday life: case study with Portuguese and Brazilian students - Canavilhas, João; Pellanda, Eduardo; Piñeiro-Naval, Valeriano; Nunes, Ana Cecília B. (Revista FAMECOS, 2020)
Mobile phones have become commonplace everyday objects in almost all societies regardless of their development stage. The presence of these devices has become a constant on any latitude, as shown by the penetration rate figures for 2018: 65.9%. These numbers, already surprising on their own, reach even higher values among young people. Thus, this paper studies the use of mobile phones, in particular smartphones, by young Portuguese and Brazilian university students. For this purpose, an app that registered all the uses made by the youngsters in their mobile devices, was employed. This methodology allows data collection in a daily context without the participants feeling controlled. A total of 317,938 interactions, registered in the participants devices, shows that the main use given to these devices is as a platform for access to social networks, followed by the sending of messages and the variable “second uses” of the device (watch, calendar, camera, calendar and calculator). Although this is a study in progress, at this stage it is safe to state that the data confirm previous studies (FORTUNATI; TAIPALE, 2014) in which smartphones assert themselves as a verbal written communication platform in opposition to their genesis based on orality. ***Telefones celulares no cotidiano dos jovens: um estudo de caso com estudantes portugueses e brasileiros*** Os telefones celulares se tornaram objetos comuns do dia-a-dia em quase todas as sociedades, independentemente do estágio de desenvolvimento. A presença desses dispositivos tornou-se constante em qualquer latitude, como mostra o índice de penetração em 2018: 65,9%. Esses números, já surpreendentes por si só, atingem valores ainda mais altos entre os jovens. Assim, este artigo estuda o uso de telefones celulares, em particular smartphones, por jovens estudantes universitários portugueses e brasileiros. Para isso, foi desenvolvido um aplicativo que registrava todos os usos feitos pelos jovens em seus dispositivos móveis. Essa metodologia permite a coleta de dados em um contexto diário sem que os participantes se sintam controlados. Um total de 317.938 interações, registradas nos dispositivos participantes, mostra que o principal uso dado a esses dispositivos é como plataforma de acesso às redes sociais, seguido pelo envio de mensagens e pela variável “segundos usos” do dispositivo (observe, calendário, câmera, calendário e calculadora). Embora este seja um estudo em andamento, é possível afirmar que os dados confirmam estudos anteriores (FORTUNATI; TAIPALE, 2014) em que os smartphones se afirmam como uma plataforma de comunicação verbal escrita em oposição à sua gênese baseada na oralidade. Palavras-chave: Estudos de Mídia. Tecnologia móvel. Estudos de comunicação.